Influence of birds on the spatial distribution of Deschampsia antarctica Desv. on Galindez Island (Argentinean Islands, Coastal Antarctic) - Parnikoza, Ivan; Abakumov, Evgeny; Dykyy, Ivan; Pilipenko, Dmitry; Shvydun, Pavlo; Kozeretska, Iryna; Kunakh, Victor (Biological Communications, 2015)
The spatial pattern of Deschampsia antarctica has been studied with the special reference to the breeding activity of two birds species — the kelp gull (Larus dominicanus) and the southpolar skua (Catharacta maccormicki). It was shown for the Galindez Island (Argentine Islands, maritime Antarctica) during the season 2013/14 that the localities and spatial pattern of the Deshampsia antarctica is related closely to zones of nesting and trophic activities of the kelp gull (Larus dominicanus). Other part of the island which is suitable for plant colonization became populated by D. antarctica by the way of casual loss of viable material by kelp gull during the transportation process. At the same time, southpolar skua may play the role of the secondary distributor of D. antarctica from coastal zone of the primary colonization into deeper parts of island. The relation of hairgrass with the breeding territories of birds also confirmed by the soil analyses data. Also some effects of antropic factor have been fixed as active on spatial distribution of D. antarcica. It is necessary to establish how the conclusions of this investigation are valuable for other zones of the maritime Antarctic. Refs 25. Figs 8. Tables 2.